Association of preoperative duration of inotropy on prevalence of right ventricular failure following LVAD implantation. (11th June 2020) - Benjamin, Mina M.; Sundararajan, Sakthi; Sulaiman, Samian; Miles, Bryan; Walker, Rebekah J.; Durham, Lucian; Kohmoto, Takushi; Joyce, David L.; Ishizawar, David; Gaglianello, Nunzio; Mohammed, Asim
Abstract: Aims: 20% to 40% of left ventricular assist device (LVAD) device implantations are complicated by right ventricular (RV) failure that results in significant morbidity and mortality. We hypothesized that the duration on milrinone infusion is an independent risk factor for RV failure following LVAD implantation. Methods and results: Retrospective demographic, clinical and hemodynamic data were collected on all adults with ACC/AHA stage D heart failure on intravenous milrinone who underwent LVAD implantation between 2012 and 2019. Patients ( n  = 104) were divided into two groups, those on milrinone <30 days (STM, n  = 55) vs. ≥30 (LTM, n  = 49). The primary endpoint was the prevalence of RV failure (need for inotropic support for more than 14 days or RV assist device) within 30 days post‐LVAD implantation. There were no significant differences between STM and LTM patients with respect to demographic, echocardiographic, right heart catheterization data, or baseline medications. The mean age of patients was 55.6 ± 12 years (70% male patients). Mean duration on milrinone was 13.7 vs. 81.0 days in STM and LTM, respectively. Forty‐five (43.3%) patients developed RV failure. LTM had higher prevalence of RV failure with odds ratio (OR) = 5.04 (95% CI 2.18–11.68, P  = 0.0002). After adjusting for age, gender, and co‐morbidity count, the OR was 6.33 (95% CI 2.51–15.93), P  < 0.0001. Conclusions: In this retrospective study of ACC/AHA stage D HF patients, longer duration of milrinone infusion was associated with higher prevalence of RV failure after LVAD implantation.